The BBNJ Agreement: Strengthening the Ocean-Climate Nexus - Scott, Karen (2022)
This paper explores the question of whether and to what extent the BBNJ Agreement, currently under negotiation under the auspices of the UN, will provide opportunities to develop and support measures relating to the mitigation of, and adaptation to, the impacts of climate change and ocean acidification on high seas biodiversity and ecosystems. While there are obvious connections between the BBNJ Agreement and climate change, particularly in respect of the parts relating to area-based protection and environmental impact assessment, this paper examines more generally the extent to which the BBNJ agreement provides an opportunity to connect the law of the sea and the climate regime, and to integrate climate concerns into high seas decision-making affecting biodiversity and ecosystems.